(untitled) (Research, Society and Development, 2020)
The present study aimed to review the effects of resveratrol supplementation in patients diagnosed with DM2. This is a systematic review, carried out using the electronic databases PubMed, Lilacs and Medline, published in English, from 2011 to 2019, with the descriptors "Resveratrol" and "Diabetes Mellitus". The inclusion criteria used were: randomized clinical trials conducted with individuals with type 2 DM. Studies with animals, pregnant women, lactating women, and individuals under the age of 18 years were excluded. It was observed that the effects of resveratrol supplementation more prevalent in these patients were related to improved insulin sensitivity, glycemic control and a possible reduction in oxidative stress. There are still controversies in the literature regarding its real effectiveness in diabetic patients. However, the use of resveratrol as an adjunct to hypoglycemic therapy is not ruled out.